2020
DOI: 10.21123/bsj.2020.17.1(suppl.).0227
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products of Lactococcus Overcome Nosocomial Infection in Some of Baghdad Hospitals in Iraq

Abstract: Nosocomial infections (NIs) are hospital-acquired associated infections, and also contracted due to the infections or toxins that exist in some location, like hospital. Therefore in our study, 4 Lactic acid bacteria (LAB) isolates were obtained from dairy product (Lactobacillus brevis, L. acidophilus, Lactococcus raffinolactis and Lactococcus lactis) and were tested for Bacteriocin production to select Lactococcus lactis among them. Cell free supernatant (CFS), Lipid and partial purification of protein La. Lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…al. 18 and Mohsin et al 19 showed that Weisella always appears in culture as white colonies, small, smooth and shiny. The presence of several fractions (contained proteins with a molecular mass less than 500 Da) may be the cause of T1 inhibition of studied bacteria; in vitro findings related to the peptidic nature of the LAB species linked to bacteria inhibition 20,21,22 , or may be occurrence the inhibition due to that some compounds work on the cell membrane and depolarize it, So, the cell wall synthesis inhibition, these compounds known as Diacetyl organic acids (lactic , formic, acetic and propionic) the pH of the medium was reduced as a result of this, So can compete for nutrients 20,23,24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al. 18 and Mohsin et al 19 showed that Weisella always appears in culture as white colonies, small, smooth and shiny. The presence of several fractions (contained proteins with a molecular mass less than 500 Da) may be the cause of T1 inhibition of studied bacteria; in vitro findings related to the peptidic nature of the LAB species linked to bacteria inhibition 20,21,22 , or may be occurrence the inhibition due to that some compounds work on the cell membrane and depolarize it, So, the cell wall synthesis inhibition, these compounds known as Diacetyl organic acids (lactic , formic, acetic and propionic) the pH of the medium was reduced as a result of this, So can compete for nutrients 20,23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…It is certain and natural that all types of probiotics prove their strong efficacy because in many sources they have proven wide range of inhibition [38][39] . It is also extended to nosocomial infection 19 , against parasite 21 , eye pathogen 22 , or against pathogenic microorganisms [40][41][42] , and proved that it gives the strongest effect when two or more types of probiotics are combined 43 . All of the previous studies that were interested in the inhibitory effect of LAB indicated that are not failed never in its role as anti-microbial agent 44 .…”
Section: Discussionmentioning
confidence: 99%